FAMILY PLANNING FIELD WORKERS’ EXPECTATIONS AND PERCEPTIONS ON SERVICE QUALITY OF TRAINING AND EDUCATION AT NATIONAL POPULATION AND FAMILY PLANNING BOARD IN PROVINCE OF CENTRAL SULAWESI, INDONESIA - Fatimah Fatimah; Arisara Leksansern (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Training and education for employees are the important thing to develop their knowledge, skill, performance as well as career. It is important to improve the quality of training and education service in National Population and Family Planning Board (BKKBN), specially training and education for field workers. Performance achievement of family planning field workers in province of Central Sulawesi until November 2018 was low, it was only 57,8% from 95% as a target for a year even though BKKBN province of Central Sulawesi implemented 10 training and education to them for improve the performance. This study aims to compare between trainees expectations and perceptions of service quality and then set up the guidelines to improve the trainig and education for family planning field workes at National Population and Family Planning Board, Province of Central Sulawesi, Indonesia.Method: This research method uses quantitative and qualitative with desciriptive design. 169 respondents filled the questionnaire with 22 statements which was pertaining with five dimensions of service quality (tangible, reliable, responsive, assurance and empathy). Moreover, focus group discussion has been used as one of qualitative methods with the management of BKKBN as participants who conduct the training and education.Conclussions: Level of expectation is in the highest level and level of perception in the highest level. Trainees expectation beyond their perceptions means that trainees did not satisfy with training and education, because perception was related with satisfaction. There was a significant differences between expectations and perceptions for tangible, reliability, responsive and assurance (p<0.05). All dimension had negative gap between expectations and perceptions (SQ= P-E). According to this gap, organiser who conduct training and education may be able to find the problem solving to improve the quality and reduce the gap between trainees expectations and perceptions and make the guidelines.